Relativistic Bound and Scattering Amplitude of Spinless Particles in Modified Schioberg Plus Manning–Rosen Potentials. (1st January 2017) - Yazarloo, B.H.; Mehraban, H.
Abstract : By using an approximation for the centrifugal term, we study relativistic bound and scattering states of spin-zero particles in the presence of equal scalar and vector modified Schioberg plus Manning–Rosen potentials for any quantum numbers n and l. Energy eigenvalues and the scattering amplitude are calculated. Some special cases of the problem are also investigated.